2019
DOI: 10.1002/chem.201900979
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structures and Melting Behaviors of 2D and 3D Anionic Coordination Polymers Containing Organometallic Ionic Liquid Components

Abstract: Although coordination polymers generally do not melt, several that do melt have been synthesized recently and have drawn much attention. In this study, two‐ and three‐dimensional coordination polymers that melt were synthesized, [Ru(Cp)(C6H5R)][M{C(CN)3}2] (R=H, Me, Et; M=K, Rb; Cp=C5H5), which are complex salts comprising M[C(CN)3] and organometallic ionic liquids [Ru(Cp)(C6H5R)][C(CN)3]. They have anionic [M{C(CN)3}2]n− coordination polymer frameworks, whose dimensionalities depend on the size of the organom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…Further studies of specific interest are as follows: (i) the diffusion of various guest species into the composite material, (ii) predicting optimum loading limits, (iii) the effects of crystallite size, and (iv) attempts at shaping the bulk products formed. We believe that this may open routes to further functional MOF-CGCs and take advantage of many recent reports of MOF and coordination polymer glass formation. …”
Section: Discussionmentioning
confidence: 85%
“…Further studies of specific interest are as follows: (i) the diffusion of various guest species into the composite material, (ii) predicting optimum loading limits, (iii) the effects of crystallite size, and (iv) attempts at shaping the bulk products formed. We believe that this may open routes to further functional MOF-CGCs and take advantage of many recent reports of MOF and coordination polymer glass formation. …”
Section: Discussionmentioning
confidence: 85%
“…We believe that this may open routes to further functional MOF--CGCs and take advantage of many recent reports of MOF and coordination polymer glass formation. [28][29][30][31]…”
Section: Resultsmentioning
confidence: 99%
“…Topological view with kgd net in complex [Ru­(Cp)­(C 6 H 6 )]­[K­{C­(CN) 3 } 2 ]. Adapted with permission from ref . Copyright 2019 John Wiley & Sons.…”
Section: Design Strategiesmentioning
confidence: 98%
“…Further H 2 and CO 2 uptake has been measured as 209.9 cm 3 (STP) g −1 and 106.8 cm 3 (STP) g 50). 377 [Zn 5 (bpib) 2 (L) 4 (OH) 2 (H 2 O) 2 ] (bpib = 1,4-bis(2-(pyridin-2-yl)-1H-imidazol-1-yl)butane; H 2 L = 3,3′-methylenebis(oxy)dibenzoic acid) provides a highly corrugated kgd net which is two-fold parallel interpenetrated (Figure 51). 378 Matzger et al reported a unique non-interpenetrated clusterbased 2D MOF [Zr 6 (μ 3 -O) 4 (μ 3 -OH) 4 (BTB) 2 (OH) 6 (H 2 O) 6 ], derived from a tritopic linker BTB (1,3,5-(4-carboxylphenyl)benzene) in the presence of concentrated HCl and exhibits kgd topology net (Figure 52).…”
mentioning
confidence: 99%